Pemecahan Masalah Matematis Ditinjau dari Kecerdasan Emosional Siswa - Sandra; Iwit Prihatin; Utin Desy Susiaty (PT. Media Edukasi Borneo, 2021)
The purpose of this study in general was to find out which was better between the Problem Based Learning model and classical learning of mathematical problem-solving abilities in terms of the emotional intelligence of students on the material system of two-variable linear equations in class VIII of one of secondary schools of Kalimantan Barat. The method used in this study was an experimental method, with a Quasi-Experimental research form, and the research design was a 2x3 factorial design. The population in this study were all eighth-grade with class samples VIII A and VIII B selected by using the Cluster Random Sampling technique. Based on the analysis of variance of two paths with unequal cells it is concluded that: 1) the problem-based learning model provides better mathematical problem-solving abilities compared to classical learning in the material system of two-variable linear equations, 2) Students with high emotional intelligence provide better mathematical problem-solving abilities compared to moderate and low emotional intelligence, 3) In each learning model, the mathematical problem-solving ability of students with high emotional intelligence is better than that of moderate and low emotional intelligence, 4) At each level of students' emotional intelligence, the Problem Based Learning model provides better mathematical problem-solving skills than classical learning. ABSTRAK Tujuan dari penelitian ini secara umum adalah untuk mengetahui manakah yang lebih baik antara model pembelajaran problem-based learning dan pembelajaran klasikal terhadap kemampuan pemecahan masalah matematis ditinjau dari kecerdasan emosional siswa pada materi sistem persamaan linier dua variable di kelas VIII di salah satu sekolah menengah pertama (SMP) Negeri Kalimantan Barat. Metode yang digunakan dalam penelitian ini adalah metode eksperimen, dengan bentuk penelitian Quasi Experimental, dan rancangan penelitian adalah desain faktorial 2x3. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP, dengan sampel kelas VIII A dan VIII B yang dipilih secara random menggunakan teknik Cluster Random Sampling. Berdasarkan analisis variansi dua jalan dengan sel tak sama disimpulkan bahwa: 1) Model pembelajaran problem-based learning memberikan kemampuan pemecahan masalah matematis yang lebih baik dibandingkan pembelajaran klasikal dalam materi sistem persamaan linier dua variable, 2) siswa dengan kecerdasan emosional tinggi memberikan kemampuan pemecahan masalah matematis lebih baik dibandingkan dengan kecerdasan emosional sedang dan rendah, 3) pada masing-masing model pembelajaran, kemampuan pemecahan masalah matematis siswa dengan kecerdasan emosional tinggi lebih baik dari padakecerdasan emosional sedang dan rendah, 4) pada setiap tingkat kecerdasan emosional siswa, model pembelajaran problem-based learning memberikan kemampuan pemecahan masalah matematis yang lebih baik dari pembelajaran klasikal. KATA KUNCI: problem-based learning, kemampuan pemecahan masalah matematis, kecerdasan emosional